Matthew Lipman and Ann Margaret Sharp Philosophy for Children's Educational Revolution - Franzini Tibaldeo, Roberto (Cham : Springer International Publishing : Imprint: Springer, 2023)
This book explores the contribution to education contained in the theoretical work and teaching practice of Matthew Lipman (1923-2010) and Ann Margaret Sharp (1942-2010). Their long-lasting cooperation gave rise to the well-known "Philosophy for Children" (P4C) curriculum, which is nowadays globally widespread. P4C basically relies on the following innovations: firstly, the unprecedented connection between philosophy and childhood; secondly, the reframing of philosophy in practical, viz., not reductively theoretical terms; thirdly, the employment of philosophy to foster democracy and moral capabilities through the development of children's thoughtfulness and autonomous thinking, which would eventually result in empowering children's social abilities and increasing their self-defence against consumerism, propaganda, and manipulation; finally, the stand against a strictly cognitivist approach to education. More than just contextualizing these innovations in the coeval historical and social context, the author shows that P4C's revolutionary stance on education relies on the fruitfulness of Lipman and Sharp's intellectual cooperation and on their manifold abilities as researchers, teachers, trainers, communicators, motivators, and community-builders. The book analyzes their philosophical-educational vision and the scholastic curriculum they developed jointly; additionally, it provides a critical appraisal of P4C's achievements as well as of its future perspectives. .
Chapter 1 -- Intellectual-biographical sketch -- (A) Matthew Lipman's early years (1923-1972) -- (B) Ann Margaret Sharp's early years (1942-1972) -- (C) Lipman and Sharp's providential meeting in 1973 -- (D) Four decades of fruitful cooperation (1973-2010) -- References. - Chapter 2 - The context of Lipman and Sharp's educational revolution -- (A) The 1960s: political and social tensions in the US -- (B) The widespread need for educational renovation -- (C) Philosophy's contribution to education -- References -- Chapter 3 - Lipman and Sharp's philosophical-educational vision -- (A) "Inside-out philosophy" -- (B) The challenge of democracy and citizenship -- (C) Cognitive self-defence and community-based philosophical enquiry -- (D) Education for reasonableness, reflectivity, fallibilism and self-correction -- (E) The multidimensionality of thinking: critical, creative and caring -- (F) Moral education, reduction of violence, appreciation of diversities -- References -- Chapter 4 - Philosophy for Children's educational curriculum -- (A) The first novel: "Harry Stottlemeier's Discovery" (1969) -- (B) The demand for empirical evaluation -- (C) The foundation of the Institute for the Advancement of Philosophy for Children (IAPC) and the development of the educational curriculum -- (D) Training supervisors and teachers -- References -- Chapter 5 - Philosophy for Children's global dissemination -- (A) Where: USA, Canada, Latin America, Africa, Europe, Asia -- (B) The reasons of P4C's worldwide success -- The effectiveness of philosophy's contribution to education -- The efficacy of P4C's community-based proposal -- P4C's methodological awareness and adaptability -- P4C's ability to cope with present-day educational challenges related to the globalised and digital age: responsibility, empowerment, interculturality, learnification -- (C) Critical and comparative remarks -- Criticisms of the P4C curriculum -- A comparison between P4C and other philosophical-educational practices -- References -- Conclusions: An open-ended educational proposal .
Keywords: Education -- Philosophy; Early childhood education; Education -- Curricula; Educational Philosophy; Philosophy of Education; Early Childhood Education; Curriculum Studies